Mental Accounting In Financial Decision Making: A Systematic Literature Review - Khadijah Darwin (www.amertainstitute.com, 2024)
Mental accounting as a cognitive process, plays an important role in individual financial decision making. This concept describes the human way manage and view their financial aspects. Individuals tend to categorize and evaluate their expenses and income in a way that is not always possible rational, forming patterns of behavior that can influence the success of decisions finance. Aim This study seeks to provide a systematic literature review regarding mental accounting in making financial decisions and adding new insights for future research. The research method uses Systematic literature review with the help of the Publish or perish application and Vosviewer is a type research used in this research. Based on the results of the analysis, it was found that mental accounting as a self-control device that individuals use to plan, make, and evaluate financial decisions. Individuals tend to use different mental accounting for each financial behavior. Besides that, understanding mental accounting has the potential to improve financial decision making, which will ultimately increase savings and welfare, as well as produce well-organized financial planning.